Territorial expansion and great power behavior during the Cold War : a theory of armed emergence - Motin, Dylan (Routledge advances in international relations and global politics, 2025)
"Motin examines the intricate relationship between the rise of new powers in bipolar international systems and the policies of the existing great powers; exploring the understudied problem of the rarity of armed emergence after 1945, he proposes a novel theory of why and when states resort to military conquest to become great powers. The book focuses on Egypt, Iraq, Syria, and Vietnam; the few minor powers that attempted to emerge as great powers through force during the Cold War. Geography and existing powers' reactions are analyzed as the two key factors determining a nation's attempts at territorial expansion to achieve power on the global political stage. This systematic investigation of previously overlooked cases has profound implications for the scholarship on the rise and fall of great powers. In a context where territorial conquest is returning worldwide, scholars studying international relations, international security, and strategic studies should find valuable insights in this realist take"--